Why history matters: ab initio rederivation of Fresnel equations confirms microscopic theory of refractive index - Starke, Ronald; Schober, Giulio Albert Heinrich (Optik, 2017)
We provide a systematic theoretical, experimental and historical critique of the standard derivation of Fresnel's equations, which shows in particular that these well-established equations actually contradict the traditional, macroscopic approach to electrodynamics in media. Subsequently, we give a rederivation of Fresnel's equations which is exclusively based on the microscopic Maxwell equations and hence in accordance with modern first-principles materials physics. In particular, as a main outcome of this analysis being of a more general interest, we propose the most general boundary conditions on electric and magnetic fields which are valid on the microscopic level.
Gesehen am 08.04.2020